Simulated Drug Discovery Process to Conduct a Synoptic Assessment of Pharmacy Students - Richardson, Alan (American Journal of Pharmaceutical Education, 2014)
Objective. To implement and assess a task-based learning exercise that prompts pharmacy students to integrate their understanding of different disciplines. Design. Master of pharmacy (MPharm degree) students were provided with simulated information from several preclinical science and from clinical trials and asked to synthesize this into a marketing authorization application for a new drug. Students made a link to pharmacy practice by creating an advice leaflet for pharmacists. Assessment. Students’ ability to integrate information from different disciplines was evaluated by oral examination. In 2 successive academic years, 96% and 82% of students demonstrated an integrated understanding of their proposed new drug. Students indicated in a survey that their understanding of the links between different subjects improved. Conclusion. Simulated drug discovery provides a learning environment that emphasizes the connectivity of the preclinical sciences with each other and the practice of pharmacy.